Anion Recognition of Two Calix[4]pyrrole-BODIPY Sensors Containing Different Steric Groups - Lv, Yongjun; Wei, Wei; Xie, Yuntao (Asian Journal of Chemistry, 2014)
The anion recognition properties of meso-octaethyl and meso-tetracyclohexyl calix[4]pyrrole-based boradiazaindacenes (BODIPY) sensors (compound 2 and 3) were investigated by absorption and fluorescence spectra. The results showed that both sensors effectively gave dual responses for F– through color changes and fluorescence quenching. Compared with meso-octamethylcalix[4]pyrrole-BODIPY sensor compounds 1, 2 exhibited a higher selectivity for F– and compound 3 showed rather weaker bonding interactions with tested anions, which can be ascribed to their steric hindrance effect of different meso-alkyl groups of calix[4]pyrrole.